AN ANALYSIS OF THE MEANING AND MESSAGE IN “A Thousand Years” SONG BY CHRISTINA PERRI - Miranda Oriza Sativa; Bima Prana Chitra (Jurnal Scientia, 2023)
This research deals with the problem of Analysis the meaning and message in A Thousand Years song lyrics by Christina Perri. Lyrics are used as primary data and use qualitative methods to explain the meaning and messages obtained using structuralism theory to find out the overall meaning in song lyrics. The researchers decided to use this method because it does not do the field research that requires real time problems and subjects. The research is mainly focus on books, journals, internet, blogs and etcThen the data and references from media such as books, journals, websites, was collected by means of a library search. And researcher get results from the meaning and message in the lyrics of the song, there are loyalty in relationships. love bravely and wait faithfully.